On an infinite dimensional linear-quadratic problem with fixed endpoints: The continuity question - Przyłuski, Maciej K. (Zielona Góra: Uniwersytet Zielonogórski)
In a Hilbert space setting, necessary and sufficient conditions for the minimum norm solution "u" to the equation "Su = Rz" to be continuously dependent on z are given. These conditions are used to study the continuity of minimum energy and linear-quadratic control problems for infinite dimensional linear systems with fixed endpoints.
Keywords: minimum norm problem; linear-quadratic control; linear-quadratic economies; controllability; continuity of optimal control